Dog bite and its interconnection with one health - Fernandes, Roberta Ribeiro; de Sá, Thaís Camaso; Pereira, Kelly Regina de Jesus Duarte; Ribeiro, Débora Cristina; Andre, Geovana Cristina Sartori; Belettini, Salviano Tramontim; Merlini, Natalie Bertelis; Maia, Luan Vinicius Tezzei; Leitzke, Arthur Venicius Sbaraini; Quessada, Ana Maria (Seven Editora, 2023)
The present review aims to analyze articles that deal with dog bite accidents in Brazil and their interconnection with unique health. Public health is a challenge for public managers. One of these challenges involves dog and cat bites on humans. In these events, medical care is needed, including the emotional aspect that can burden the budget of municipalities in the health area. Knowledge about dog and cat bites is important for the development of strategies aimed at unique health with the implementation of educational measures. Animal bites (domestic and wild) are common in Brazil and are important in emergency medical care. Through bites, humans can be infected with infections of bacterial, viral, fungal, and parasitic origin. The complexity of bites is related to the degree of contamination and its polymicrobial nature, being the most serious complication related to infection. Psychological sequelae, physical disabilities and, more rarely, the death of victims can occur. In Brazil, aggression by animals is most often caused by dog bites and most victims are males of different age groups. DOI: https://doi.org/10.56238/devopinterscie-095